Borçlar Hukukunda aldatma - Sak, Burak (My University, 2024)
Borçlar Hukukunda Aldatma isimli bu doktora tezinde Türk Borçlar Kanunu m. 36 düzenlemesi iki bölüme ayrılarak incelenmiştir. aldatma kavramı ve unsurları ortaya koyulmuş, İkinci Bölüm’de ise aldatma hükmünün uygulanmasının sonuçları ele alınmıştır. Aldatmanın unsurları beşe ayrılmıştır. Buna göre; kasıtlı ve hukuka aykırı davranış, saik yanılması, hukuki işlemin kurulması, nedensellik bağı ve üçüncü kişinin aldatmasında karşı tarafın kötüniyeti aldatmanın unsurlarıdır. Aldatmanın unsurlarının bir arada bulunması hâlinde aldatma hükmü uygulama alanı bulur ve bunun sonuçları da İkinci Bölüm’de değerlendirilmiştir. Bu değerlendirmeler kapsamında aldatmanın sonuçları; henüz sona ermemiş iptal hakkının ileri sürülmediği esnada hukuki işlemin tabi olduğu hükümsüzlüğün türü, iptal hakkına dair meseleler ve aldatılanın uğradığı zararın tazmini üzerinde durulmuştur.

In this PhD thesis titled “Deception in the Law of Obligations” Article 36 of the Turkish Code of Obligations is analyzed in two parts. In the first part, the concept and elements of deception are presented, and in the second part, the consequences of the application of the deception provision are discussed. The elements of deception are divided into five. Accordingly, the elements of deception are intentional and unlawful behavior, mistake of motive, the establishment of a legal transaction, causal link and the bad faith of the other party in the deception of the third party. In the event that the elements of deception coexist, the provision on deception is applicable, and the consequences of deception are evaluated in the Second Section. Within the scope of these evaluations, the consequences of deception; the type of nullity to which the legal transaction is subject during the non-assertion of the right of cancellation that has not yet expired, the issues regarding the right of cancellation and the compensation of the damage suffered by the deceived are discussed.
Deception in the law of obligations
Keywords: 36 TCO; aldatılanın uğradığı zararın tazmini Art; aldatma; aldatmanın unsurları; Borçlar hukuku; compensation for the damage suffered by the deceived; deception; elements of deception; iptal hakkı; Obligations (Law); right of cancellation; TBK m. 36; Turkey; Türkiye